3D Micro-CT Analysis of Void and Gap Formation in Curved Root Canals - Şimşek, N.; Keleş, A.; Ahmetoǧlu, F.; Akinci, L.; Er, K. (Kare Publishing, 2017)
Objective: This study used microcomputed tomography (micro-CT) to compare the volumes of voids and gaps in curved root canals instrumented and filled using various techniques. Methods: Twenty extracted mandibular first molars with two curved mesial root canals were used. Root canals were instrumented using a self-adjusting file (SAF) or Revo-S file system. For standardization, mesiobuccal canals were instrumented with SAF and mesiolingual canals were instrumented with Revo-S in each root. The canals were divided into four experimental groups (n=10 in each). The canals were then filled via cold lateral compaction (CLC) or a thermoplasticized injectable technique (TT) using gutta-percha and AH Plus root canal sealer. The roots were scanned with a micro-CT, and the volumes of the voids and gaps were calculated using three-dimensional (3D) micro-CT images. Data were analyzed using unpaired t- and Kruskal-Wallis tests. A value of P < 0.05 was considered significant. Results: None of the tested techniques provided void- or gap-free fillings. Nevertheless, the SAF showed more gap formation than the Revo-S, and TT showed higher gap formation in all experimental groups. These differences, however, were not statistically significant (p>0.05). Conclusion: The SAF and Revo-S rotary file systems yielded comparable results. No statistically significant difference was found between the results of the various instrumentation and filling techniques. © 2017 Kare Publishing. All rights reserved.
Keywords: Gap; Micro-CT; Quality of Obturation; Revo-S; Self-Adjusting File; Void